Angiosarcoma in Long-Standing Nodular Regenerative Hyperplasia. Issue 10 (18th October 2022) - Abdul Majeed, Nehna; Kleiner, David E.; Uzel, Gulbu; Koh, Christopher; Heller, Theo
ABSTRACT: Nodular regenerative hyperplasia (NRH) is an uncommon chronic liver disease associated with noncirrhotic portal hypertension. A 29-year-old man with X-linked agammaglobulinemia and NRH complicated by noncirrhotic portal hypertension was followed. Laboratory test results showed pancytopenia and elevated transaminases. Magnetic resonance imaging showed innumerable hepatic lesions. Liver biopsy showed angiosarcoma (hepatic angiosarcoma). He was not a candidate for medical or surgical intervention because of extensive disease and died. Liver histology at autopsy showed infiltrating foci of angiosarcoma. This report extends the literature on a link between malignancy and NRH.